Possibilities for CO2 emission reduction using biomass in European integrated steel plants. (August 2018) - Mandova, H.; Leduc, S.; Wang, C.; Wetterlund, E.; Patrizio, P.; Gale, W.; Kraxner, F.
Abstract: Iron and steel plants producing steel via the blast furnace-basic oxygen furnace (BF-BOF) route constitute among the largest single point CO2 emitters within the European Union (EU). As the iron ore reduction process in the blast furnace is fully dependent on carbon mainly supplied by coal and coke, bioenergy is the only renewable that presents a possibility for their partial substitution. Using the BeWhere model, this work optimised the mobilization and use of biomass resources within the EU in order to identify the opportunities that bioenergy can bring to the 30 operating BF-BOF plants. The results demonstrate competition for the available biomass resources within existing industries and economically unappealing prices of the bio-based fuels. A carbon dioxide price of 60 € t −1 is required to substitute 20% of the CO2 emissions from the fossil fuels use, while a price of 140 € t −1 is needed to reach the maximum potential of 42%. The possibility to use organic wastes to produce hydrochar would not enhance the maximum emission reduction potential, but it would broaden the available feedstock during the low levels of substitution. The scope for bioenergy integration is different for each plant and so consideration of its deployment should be treated individually. Therefore, the EU-ETS (Emission Trading System) may not be the best policy tool for bioenergy as an emission reduction strategy for the iron and steel industry, as it does not differentiate between the opportunities across the different steel plants and creates additional costs for the already struggling European steel industry. Graphical abstract: Image 1 Highlights: Full biomass demand by iron and steel plants can be met in the EU. Use of bio-products in steel plants is viable only at a high CO2 price. Hydrothermal carbonisation of waste could help initial fossil fuel substitution. Maximum CO2 emission reduction possible is 91 Mt per year (42%). Imposing required CO2 price would significantly impact steel production costs.